Differential expression of several factors involved in placental development in normal and abnormal condition. (June 2020) - Hay, Eleonora; Lucariello, Angela; Contieri, Marcella; Trucillo, Marta; Pavese, Ludovica; Guerra, Germano; De Falco, Maria; De Luca, Antonio; Perna, Angelica
Abstract: The placenta, a temporary organ that forms during pregnancy, is the largest fetal organ and the first to develop. It is recognized as an organ that plays a vital role as a metabolic and physical barrier in the fetoplacental unit; throughout fetal development it acts as the lungs, gut, kidneys, and liver of the fetus. When its two components, the fetal and the maternal one, successfully interact, pregnancy proceeds healthily. However, in some cases there may be pregnancy disorders, such as preeclampsia (PE) and gestational diabetes mellitus (GDM), which can lead to a different outcome for the mother and the newborn. In recent years, several studies have been conducted to try to understand how the expression of factors involved in the development of the placenta varies under pathological conditions compared with normal conditions. The purpose of this review is to summarize recent discoveries in this field.